Obtenção de scaffolds poliméricos baseados em poli(ácido lático), hidroxiapatita e óxido de grafeno utilizando o método de manufatura aditiva por “fused deposition modeling” - Siqueira, André da Silva (2018)
The present work aims to obtain and characterize a composite filament based on poly (lactic acid) (PLA), hydroxyapatite (HA) and graphene oxide, to process it by fused deposition modeling (FDM), and then make scaffolds for bone tissue growth and order to evaluate the properties of the obtained structure. To achieve these goals composite of PLA/HA, PLA/GO and PLA / HA / GO with concentrations of 0.05 wt %, 0.1 wt % and 0.3 wt % GO and 30 wt % HA were obtained by melt state blending and subsequently processed by FDM. The graphite oxide was obtained by modified Hummers method and characterized by X-ray diffraction (XRD), thermogravimetric analysis and Raman spectroscopy. The PLA and composites were characterized by molar mass measurements, infrared and Raman spectroscopy, tensile strength tests, contact angle measurements (surface energy), differential scanning calorimetry (DSC) and rheological tests. The insertion of GO into PLA and PLA/HA composites led to improvements in the mechanical properties (tensile) and also modified significantly the surface properties of the materials and the composition with 0.05 wt % of GO has shown the better results in both characteristics. These improvements occurred due to the strong interaction of the GO sheets with the PLA matrix that indicates the process of obtaining the composites via the melting state was correctly conducted. All PLA / HA / GO compositions presented rheological characteristics compatible with of scaffolds production process via FDM. The insertion of the GO into the PLA matrix and the PLA / HA composite has been shown to be extremely promising, and possibly to increase the variety of PLA / HA based biomaterials application.